Teachers’ perspectives of assessment and alternative assessment in the classroom - Sulaiman, Tajularipin; Abdul Rahim, Suzieleez Syrene; Hakim, Muhammad Nazrul; Omar, Rosmaria (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This study aims to explore teachers’ perspectives of the elements in assessment, choice of the types of assessment and perspectives of alternative assessment. The study was a case study involving seven in-service secondary school teachers who were interviewed. The findings indicate that respondents develop questions based on bloom’s taxonomy and higher order thinking. Formative and summative assessment are used to create a more comprehensive classroom assessment. Also, the respondents view alternative assessment as consisting of various techniques. © BEIESP.